Enhanced electrochemical performance of polypyrrole coated MoS2 nanocomposites as electrode material for supercapacitor application - Thakur, Anukul K.; Choudhary, Ram Bilash; Majumder, Mandira; Gupta, Govind; Shelke, Manjusha V. (Journal of Electroanalytical Chemistry, 2016)
Binary nanocomposites of polypyrrole (PPY) and Molybdenum disulfide (MoS2), with varying weight% of MoS2 viz. MP1, MP2, and MP3 corresponding to 12.5, 25, and 50% of MoS2 respectively, were prepared via. in-situ polymerization method. X-ray diffraction (XRD), field emission scanning microscopy (FESEM), and transmission electron microscopy (TEM) were employed to study the structure and morphology of the prepared nanocomposites. The electrochemical properties were studied by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS) techniques. The nanocomposite electrode material MP2 reached a specific capacitance of 400 F/g at the current density 1 A/g which was higher than that of pure PPY and the other two nanocomposites viz. MP1 and MP3 having different compositions of MoS2 and PPY than that of MP2. It was noteworthy that the maximum capacitance value was obtained only for an optimum dose of MoS2 (MP2 in this case with 25% of MoS2) and any deviation from which ultimately degraded the capacitive performance of the nanocomposite electrode material. This could be attributed to the occurrence of maximum interaction between MoS2 and PPY in the nanocomposite only at a particular concentration of its host materials. The results showed that the specific capacitance of MP2 nanocomposite declined by 7.2% after 5000 cycles. Further, MP2 nanocomposite electrode showed much higher energy density (8.88 Wh/kg) as well as power density (2286 W/kg) which were higher than that shown by PPY electrode. (C) 2016 Elsevier B.V. All rights reserved.